The Fattening and Slaughtering Examination at the Hungarian Racka Sheep - Nagy, László; Domanovszky, Ádám; Székely, Pál (Acta Agraria Debreceniensis, 2004)
Fattening and slaughtering characteristics of both types (black and white) of the Hungarian racka sheep were investigated at the site of the National Institute for Agricultural Quality Control in Atkár. The Hungarian merino, the dairy cigaja and the British milksheep were applied as control groups. 10 animals were examined from both sexes in each genotype. The examination was carried out according to the principles set in the Codex for sheep breeding. During the test acute diarrhoea occurred in each control group. However, only few lambs were excluded from the test from the British milksheep and the Hungarian merino groups because of significant changes in their condition. Consequently, the results obtained were not significantly influenced. No symptoms of any illness could be recognised in the Hungarian racka sheep, though. The significance of the difference between the average of the examined groups were checked by T-tests.Daily gain was significantly less compared to the control groups, except for the white racka males. The lambs starving for 24 hours before slaughtering weighed 25.3-30.0 kgs on average. The black and white racka females weighed the least while the Hungarian merino females weighed the most. The quantity of abdominal and kidney fat was significant in the case of our native females. The quantity of abdominal fat was significantly bigger compared to each control group. On comparing the investigated groups it turned out that the white racka males had the biggest skin weight while the white Hungarian racka females had the smallest, that is the two extremes were recognised in the same colour (white) of one bred. On qualifying the slaughtered animals females had better results than males in each bred; the racka sheep were better than the dairy cigaja but were worse than the Hungarian merino and British sheep groups.The huge differences in the carcasses of the groups were seen clearly when chopping. Examining the leg, it was noticed that the native groups proved to be smaller than the control groups, except for the black racka males. As for the short loin, the Hungarian racka and the Hungarian merino sheep proved to be the best, whereas the dairy cigaja and the British milk males had much smaller ones. The results gained when investigating the rack were similar to those of the short loin. As far as the rib and shoulder are concerned, the black racka females and the dairy cigaja females had the worst results. After chopping, the right side was also boned in every group. The small proportion of bone in the case of racka sheep was easily noticeable that resulted in the fact that the white racka females had the highest quantity of short loin compared to the other groups. When examining the back quarter, the bone proportions of the 4 racka groups proved to be significantly less than those of the control groups but it was not true for the meat proportions. As for the front quarter meat, the racka males were prominent in the great shoulder meat and in the small proportion of bone. The quantity of the first quarter bone was the least in the case of racka sheep and was the biggest for dairy cigajas. This difference proved to be significant in most cases.In short, the Hungarian racka groups had the best results in meat quantity, which was especially significant compared to the dairy cigaja sheep. However, the quantity of external fat increased.